Peran Guru PAI dalam Membentuk Karakter Religius Peserta Didik di Era Digital - Fathoni, Achmad Rafli (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
This article is about the role of teachers in shaping students' religious characteristics in the digital era. The digital era brings new challenges in the formation of students' religious character, it requires Islamic Religious Education teachers to adapt and develop innovative strategies. This study aims to analyse the role, strategies, as well as evaluation and development of PAI teachers in shaping learners' religious character in the digital era. This article uses the literature study method to identify and analyse various aspects of challenges, the role of PAI teachers, learning strategies, and evaluation and development methods in the context of religious education in the digital era. The results show that PAI teachers have multifaceted roles as role models, facilitators, mentors, motivators, connectors, filters, and evaluators in religious character building. The discussion leads to the importance of a holistic approach in the formation of religious character in the digital era. PAI teachers need to continuously develop their competence to integrate religious values with the reality of modern technology.